Preparedness of primary health care facilities on implementation of essential non-communicable disease interventions in Osun State South-West Nigeria: a rural-urban comparative study - Adebowale Femi Akinwumi; Olapeju Adefunke Esimai; Olujide Arije; Temitope Olumuyiwa Ojo; Oluwaseun Taiwo Esan (BMC, 2023)
Abstract Background Global response to the growing burden of non-communicable diseases (NCDs) in developing countries includes the development of WHO Package of Essential Non-communicable Disease Interventions (WHO PEN) for Primary Health Care (PHC). The study assessed the level of preparedness of PHC facilities on implementation of essential NCD interventions in rural and urban Local Government Areas (LGAs) of Osun State, Nigeria. Methods The study was a comparative cross-sectional survey. Information was collected from heads of 33 rural and 33 urban PHC facilities and through direct observation on the domains of staff training, basic equipment, diagnostics and essential medicines for cardiovascular diseases, diabetes and chronic respiratory diseases (CRDs) using a semi-structured interviewer administered questionnaire. Results Manual sphygmomanometer was found in similar proportions (84.8%) of PHC facilities in rural and urban LGAs. Glucometer was available in 45.5% of the PHC facilities in urban and 33.3% of the PHC facilities in the rural LGAs, the difference was not statistically significant (χ2 = 1.015; p = 0.314). Basic equipment for CRDs were not available in majority of PHC facilities in both locations. Moduretic tablets were the most reported essential NCD medicines, available in 15% of PHC facilities in rural LGAs and none in urban LGAs. The anti-diabetic medicines were not available in any of the PHC facilities in both locations. More than 90% (≥ 30) of the PHC facilities in both locations were not prepared to implement essential interventions for each NCD across domains of staff training and essential medicines. Overall, 97.0% of the PHC facilities in the rural LGAs and all the PHC facilities in urban LGAs were not prepared on implementation of essential interventions for the three NCDs. Conclusion The level of preparedness of the PHC facilities on implementation of essential NCD interventions in the rural and urban LGAs of Osun State is very low. Government needs to strengthen the PHC system by providing needed essential medicines, basic diagnostics, equipment, and training of clinical health care workers for implementation of essential NCD interventions in the state.